Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Ibu Hamil Trimester III Tentang Cara Menyusui Di Wilayah Puskesmas Watas Marga Tahun 2024 - Triyunila, Triyunila; Nurjanah, Nimas Ayu Lestari; Sari, Liya Lugita (Universitas Dehasen Bengkulu, 2025)
Breast milk is the main source of nutritional needs for babies, because it contains white blood cells, immunoglobin, enzymes and hormones as well as other proteins needed in the process of optimal child growth and development. Breastfeeding failure can be influenced by internal and external factors. A common problem during the breastfeeding process is the inappropriate way of breastfeeding. Health workers are expected to provide information in the form of health education on how to breastfeed properly to pregnant women so that they can breastfeed their babies, so that problems that occur during the breastfeeding process can be avoided, and can increase the coverage of exclusive breastfeeding for 6 months in newborns. The purpose of this study is to determine the effect of health education on the knowledge of third trimester pregnant women about how to breastfeed. This type of research is quantitative, the design used in quasi-experiment research. The quasi-experiment design used was one group pretest and posttest design. The number of samples in this study were 38 third trimester pregnant women in Watas Marga Health Center. The results of the study obtained after being given health education on how to breastfeed increased to 77.53 (Good Knowledge) with a deviation standard of 7.721. The results of the statistical test obtained p-value of 0.000, it can be concluded that health education can affect the mother's knowledge about how to breastfeed